Sexual Violence and the Politics of Criminal Law in Indonesia: A Gender Equality Approach and Maqāsid al-Sharī’a - Kamalludin, Iqbal; Pratami, Bunga Desyana; Alviolita, Fifink Praiseda; Christia, Adissya Mega; Umar, Achmad Jauhari (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
This article examines the criminal law policy in Indonesia regarding the increasing incidence of sexual violence crimes, primarily affecting women. The study adopts a literature research approach, utilizing data from legal regulations in Indonesia and various scholarly works related to the subject. Employing a gender equality approach and maqāsid al-sharī'a, the article concludes that while Indonesia possesses legal regulations addressing sexual crimes, these laws are dispersed across different statutes, resulting in diminished effectiveness. The enactment of the Law on Sexual Violence (UU TPKS) in 2022 signifies a noteworthy development in Indonesia's legal framework concerning sexual violence. This legislation is structured in a more organized and comprehensive manner, incorporating several reforms. Consequently, it instills optimism for enhanced endeavors to eliminate and prevent sexual violence. From an Islamic standpoint, the regulation of sexual violence aligns with the fundamental principles and objectives of Islamic law (maqāsid al-sharī'a). These principles aim to actualize the well-being and benefit of humanity while simultaneously preventing crimes that pose threats to human existence and dignity.   Artikel ini mengkaji kebijakan hukum pidana di Indonesia dalam mengatasi praktik tindak pidana kekerasan seksual yang cenderung meningkat dari waktu ke waktu dan perempuan adalah pihak yang paling banyak menjadi korban tindak kejahatan ini. Artikel ini merupakan penelitian kepustakaan yang sumber datanya didasarkan pada peraturan-peraturan hukum di Indonesia dan sejumlah karya ilmiah yang berkaitan dengan topik kajian ini. Menggunakan pendekatan kesetaraan gender dan maqāsid al-sharī’a artikel ini menyimpulkan bahwa Indonesia sebenarnya telah memiliki sejumlah peraturan hukum tentang tindak pidana kejahatan seksual. Namun demikian, aturan-aturan hukum tersebut disusun secara parsial dan tersebar di berbagai peraturan perundang-undangan sehingga menjadikannya kurang efektif. Lahirnya Undang-undang Tindak Pidana Kekerasan Seksual (UU TPKS) pada tahun 2022 menandai adanya perkembangan baru dalam pengaturan hukum tindak pidana kekerasan seksual di Indonesia. Undang-undang ini disusun secara lebih sistematis dan komprehensif dengan sejumlah pembaruan yang ada di dalamnya sehingga ia telah memberikan harapan baru bagi upaya pemberantasan dan pencegahan terhadap praktik kekerasan seksual. Dalam perspektif Islam, pengaturan tentang tindak pidana kekerasan seksual ini selaras dengan prinsip dasar dan tujuan disyariatkannya hukum Islam (maqāsid al-sharī’a), yang ingin mewujudkan kebaikan dan kemaslahatan umat manusia dan sekaligus mencegah terjadinya tindakan kejahatan yang bisa mengancam eksistensi dan kehormatan manusia.